Relationship of the influence of physical activity with cardiovascular risk factors in adult citizens of Melilla - Fernández Gómez, E.; Sánchez-Ojeda, M.A.; Martín-Salvador, A.; Enrique Mirón, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
Physical activity has a positive influence on people's health, playing a key role in the prevention, treatment, control and rehabilitation of chronic non-communicable diseases. The aim of the study is to analyse the relationship between the practice of physical activity and cardiovascular risk factors. Cross-sectional and correlational study using a questionnaire with a sample of 160 participants. The results show that 70% of the sample stated that they did not do much physical activity compared to 33% who stated that they did moderate/high levels of physical activity. Of the variables related to cardiovascular risk, sex, glycemia and systolic blood pressure are significantly associated with the degree of physical activity (p<.05). It is essential to strengthen health education for the entire population in order to maintain adequate physical activity and other healthy lifestyles that will have an impact on reducing preventable chronic diseases.